2022
DOI: 10.1177/03635465221097102
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Return to Manual Labor After Arthroscopic Rotator Cuff Repair

Abstract: Background: Rotator cuff tears represent a significant cause of shoulder pain and dysfunction in the United States. The development of these injuries is associated with older patient age and higher levels of physical activity; however, data regarding the rate of return to work after arthroscopic rotator cuff repair in patients older than 50 years of age who have physically strenuous jobs is inconclusive. Purpose/Hypothesis: The purpose of this study was to report short term outcomes and return to work rates af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
(59 reference statements)
1
9
1
Order By: Relevance
“…The irst aspect taken into consideration in this study was the time to RTW: with a retrieved mean of 4.7 months, which appears to be in line with the majority of the literature, that reports a range of 5-11 months [15,18,30]. It is not surprising that the time to RTW progressively increased as the physical efort increased, as underlined by Novè-Josserand et al [26], who reported a time away from fulltime work of 7 months for non-manual workers, 9.2 months for manual workers, and 11.2 months for heavy manual workers.…”
Section: Discussionsupporting
confidence: 80%
“…The irst aspect taken into consideration in this study was the time to RTW: with a retrieved mean of 4.7 months, which appears to be in line with the majority of the literature, that reports a range of 5-11 months [15,18,30]. It is not surprising that the time to RTW progressively increased as the physical efort increased, as underlined by Novè-Josserand et al [26], who reported a time away from fulltime work of 7 months for non-manual workers, 9.2 months for manual workers, and 11.2 months for heavy manual workers.…”
Section: Discussionsupporting
confidence: 80%
“…However, only 57.6% of the intact group and 56.2% of the retear group in our study population could fully return to their previous work without limitations in intensity or time, and only 50.0% of the intact group and 23.1% of the retear group could fully return to their preinjury level of sports. These rates are lower than previously reported in other studies that reported return-to-work rates of approximately 62.3% to 89.6% 17,20 and return-tosports rates of approximately 65.9% to 93%. [3][4][5][6]31 This difference may be because of our study design, which had patients self-report their work and sports status without controlling for personal bias or secondary gain.…”
Section: Discussioncontrasting
confidence: 76%
“…Furthermore, and to the best of our knowledge, except for Green et al 20 the literature does not mention the surgical repair of a ruptured tendinopathy—retained in our study in the multiple factor model—as a factor favorable to return to/remain at work; it is a major surgical procedure, causing a longer duration of immobilization and a longer duration of complete recovery 25 than for a nonruptured tendinopathy. At the preoperative stage, this variable did not predict the duration of time off work postsurgery 28 .…”
Section: Discussionmentioning
confidence: 84%
“…By contrast, with a mean follow-up of 34 months, Green et al 20 concluded that 89.6% of manual workers were able to return to work after arthroscopic rotator cuff repair.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation